IDENTIFIKASI KONSEP BIOLOGI YANG DIANGGAP SULIT OLEH SISWA SEKOLAH MENENGAH ATAS: A SYSTEMATIC LITERATURE REVIEW - Hallaby, Syarifah Fadiya; Hamama, Syarifah Farissi (Jurnal Dedikasi Pendidikan, 2025)
As a field of natural sciences that studies living things, biology not only plays an important role but also basis for various essential applied fields such as agriculture, medical, biotechnology and environmental science. However, biology is also a subject that is often reported difficult to learn. This study aims to identify biology concepts that are considered difficult by high school students in Indonesia through a literature review in the form of a Systematic Literature Review (SLR). The results of the analysis of the selected articles show that the concepts that are considered difficult are distributed at all grades in high school level. The concepts of viruses, plantae, animalia, invertebrate, cells, animal tissue structure and function, excretory system, movement system, disorders in the circulatory system, immune system, cell division, metabolism, enzymes, growth and development of organism and plant tissue culture are biological concepts that are considered difficult by high school students. The factors that cause certain biological concepts are difficult to learn as well as the efforts to overcome the difficulties in the biology learning process related to these concepts are analyzed in this study